Islamic Financial Engineering at the Crossroads: Between the Need for Hedging and the Compliance Requirements - Kafou, Ali (Journal of Islamic Finance, 2022)
Financial engineering is a vital need for the prosperity of Islamic finance. It offers solutions to create new opportunities, expand the existing market and create market niches for Islamic financial institutions. Despite its importance, the literature on Islamic financial engineering is scarce, and almost nothing exists from a practice perspective as this aspect is very secretive within Islamic financial institutions. The present paper is a theory-based-research attempting to gather, analyze in depth and present the thematic of Islamic financial engineering and related issues to its application, especially for market risk hedging. We first start with the theoretical background of Islamic financial engineering to identify its principles and understand the challenges it faces. As a case study, we delimit our research to Islamic explicit derivatives, which are designed instruments to hedge market risk. The analysis of those instruments shows that the current path of Islamic financial engineering is towards imitation and replication of conventional products rather than designing genuine conceptual alternatives. Finally, we argue that the imitation strategy is not inevitable; it is possible to do without within the mutuality framework.